Kinerja Simpang Tiga Tak Bersinyal Bukit Siguntang (Jalan Srijaya Negara- Jalan Demang Lebar Daun) Palembang - Arief Aszharri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
One of the intersections in the city of Palembang is the Three-way Intersection of Bukit Siguntang, which is a signal-free intersection. This intersection is located in an educational and residential area, connecting Srijaya Negara Street and Demang Lebar Daun Street. The road has a very high volume of vehicles, with traffic flows reaching 45,208 vehicles on Sundays or holidays, 82,124 vehicles on Mondays, and 80,379 vehicles on Wednesdays. Among these three days, Monday is the busiest day with a vehicle count of 84,364. The intersection's performance is evaluated by examining the capacity levels at each approach. The Three-way Intersection of Bukit Siguntang shows a degree of saturation (DS) above 0.85 on all approaches, indicating that the road capacity has reached a saturation level resulting in a service level of D for the intersection, with an average intersection delay of 34.27 seconds/vehicle. To enhance the intersection capacity, several alternatives can be implemented, including road geometric widening and changing the traffic flow policy from two-way single lane to one-way single lane. Simulation of the capacity improvement for the intersection with both alternatives indicates that road geometric widening results in a delay of 24.58 seconds/vehicle, falling within the service level C for the intersection. Meanwhile, changing the traffic flow policy from two-way single lane to one-way single lane results in a delay of 17.39 seconds/vehicle, also falling within the service level C for the intersection.